Food protein-induced enteropathy: a revision for the clinician - Barni, Simona; Mori, Francesca; Pecoraro, Luca; Saretta, Francesca; Giovannini, Mattia; Arasi, Stefania; Liotti, Lucia; Mastrorilli, Carla; Klain, Angela; Gelsomino, Mariannita; Castagnoli, Riccardo; Miraglia del Giudice, Michele; et al. (Frontiers in Pediatrics, 2024)
Food protein-induced enteropathy (FPE) belongs to non-IgE gastrointestinal mediated food allergies. FPE is a syndrome characterized by diarrhea, weight loss and failure to thrive in young infants. Cow milk is the culprit food that most frequently causes FPE.The prevalence of FPE has not been fully estimated, but it is relatively rare. The diagnosis is based on the clinical manifestations and histological findings through colonoscopy. Laboratory tests are somewhat helpful in the diagnosis, although there are no disease-specific findings. Allergy testing for food specific IgE is not routinely recommended. The cornerstone of the management of FPE is the removal of culprit food from the diet. FPE is usually a transient condition that resolves in most cases by 1-2 years of life. This review addresses the latest findings on FPE, including a practical guide to assist pediatricians treating children with FPE.